Method for preparing modacrylic-LLZTO composite solid electrolyte membrane from waste modacrylic material and application of modacrylic-LLZTO composite solid electrolyte membrane
The preparation of nitrile chlorine-LLZTO composite solid electrolyte membrane through cleaning and electrospinning technology has solved the problems of waste nitrile chlorine recycling and interface stability of lithium metal batteries, and achieved high-quality recycling and long-life needs of lithium metal batteries.
Patent Information
- Application Number
- CN202411169798.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-25
AI Technical Summary
In the prior art, the recycling method of waste nitrile chlorine has problems of low quality, high cost and environmental pollution, and the interface degradation between the polymer and the lithium negative electrode in the composite solid electrolyte results in interface instability, affecting the circulation of lithium metal batteries. life.
By cleaning and disposing of waste nitrile chlorine material, electrospinning technology is used to prepare nitrile-LLZTO composite solid electrolyte membrane, and inorganic ceramic fillers LLZTO and lithium bistrifluoromethanesulfonimide (LiTFSI) and polyethylene oxide are used to prepare inorganic ceramic fillers LLZTO and lithium bistrifluoromethanesulfonimide (LiTFSI) and polyethylene oxide Materials such as (PEO) form organic-inorganic composite nanofiber membranes to improve the ion transport capability and mechanical flexibility of the electrolyte.
It has achieved high-quality recycling and utilization of nitrile chlorine-LLZTO composite solid electrolyte membrane, with good tensile flexibility and ion transmission capabilities, extending the cycle life of lithium metal batteries, and reducing production costs.
Smart Images

Figure CN119253026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an energy storage system device material, and in particular to a method for preparing an acrylonitrile-LLZTO composite solid electrolyte membrane using waste acrylonitrile material and application thereof, belonging to the technical field of energy storage system device material preparation. Background Art
[0002] The rapid development of the textile industry and fast fashion has resulted in about 92 million tons of textile waste generated each year. About 85% of the waste is disposed of by landfill and incineration, which causes serious environmental pollution and waste of resources. However, more than 90% of the textile waste disposed of in landfills can be reused or recycled. Even after the treatment, discarded clothing still has a potential service life of about 70%. Modacrylic is a fiber made by emulsion polymerization of vinyl chloride and acrylonitrile and then spinning by warm or dry spinning. Its main components are vinyl chloride and acrylonitrile, usually with a vinyl chloride content of 40% and an acrylonitrile content of 60%. This fiber is between chlorofiber and acrylic fiber, has good heat resistance and flame retardancy, and is elastic, so it is widely used in a variety of application scenarios. Regarding the recycling methods of waste modacrylic, there are currently several options, including physical recovery, chemical recovery, and energy recovery. However, these methods have problems such as low quality, high cost, and environmental pollution. Therefore, it is of great significance to adopt sustainable management methods for simple and green preparation and high-value reuse of waste chlorofluorocarbon.
[0003] Inorganic-polymer composite solid electrolytes are usually prepared by dispersing conductive or non-conductive inorganic nanoparticles in an organic polymer matrix to improve the overall ionic conductivity and impart mechanical flexibility. However, the interfacial degradation between the polymer and the lithium anode in the composite solid electrolyte may lead to interfacial instability. Therefore, one of the current research directions is to construct interfacial self-reinforced membranes to promote ion transport and improve the cycle life of lithium metal batteries. Summary of the invention
[0004] The present invention provides a nylon-LLZTO composite solid electrolyte membrane. The electrolyte membrane is prepared from waste nylon material, has good tensile flexibility, and can be bent and folded. When used as a solid electrolyte material for an all-solid-state lithium metal battery, the LLZTO composite solid electrolyte membrane has good ion transmission capability and can meet the needs of a long-life lithium metal battery.
[0005] The invention also provides a method for preparing a nylon-LLZTO composite solid electrolyte membrane by using waste nylon material.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A method for preparing a nylon-LLZTO composite solid electrolyte membrane using waste nylon material and its application, the method comprising the following steps:
[0008] S1. Cleaning of waste acrylic fiber
[0009] The dyed or colorless acrylic fiber, yarn or fabric (collectively referred to as acrylic fiber) to be recycled is washed with running water to remove impurities, then immersed in anhydrous ethanol for 12h-15h, and vacuum dried to obtain clean acrylic fiber;
[0010] S2. Preparation of organic-inorganic composite nanofiber membrane
[0011] Adding S1 treated nylon, inorganic ceramic filler LLZTO and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) into solvent N,N-dimethylformamide (DMF), and stirring them fully at a temperature of 35-80° C. to obtain a uniformly mixed spinning precursor solution; wherein the weight ratio of nylon to LLZTO is 1:0.02-0.3, and the addition amount of LiTFSI accounts for 0.2-3% of the mass of nylon;
[0012] The spinning precursor solution is electrospun to prepare a nylon / LZTO nanofiber membrane, and then vacuum dried at 45±5° C. to obtain an organic-inorganic composite nanofiber membrane;
[0013] S3. Preparation of electrolyte solution
[0014] Polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB) and succinonitrile (SN) were dried in vacuum within a suitable temperature range and then used.
[0015] PEO, LiTFSI and LiDFOB are uniformly stirred in an appropriate amount of solvent until they are completely dissolved, and then SN is added and stirred until uniformly dispersed to obtain a dual lithium salt PEO-based electrolyte solution;
[0016] Based on the mass of PEO being 100%, the amount of SN is 10-80%, the amount of LiTFSI is 10%-50%, and the molar ratio of LiDFOB to LiTFSI is 1:18-20.
[0017] S4. Preparation of composite solid electrolyte membrane
[0018] The organic-inorganic composite nanofiber membrane prepared in S2 is placed on a polytetrafluoroethylene mold, and a layer of electrolyte solution prepared in S3 is cast on the surface; after the solvent is completely evaporated, vacuum drying is performed at a temperature of 40-50°C to obtain a nitrile-LLZTO composite solid electrolyte membrane of a dual lithium salt system.
[0019] Vinyl chloride and acrylonitrile in acrylic fiber are the same as PAN and PVC, but the cost of acrylic fiber is relatively low. The application of PAN and PVC in energy storage devices makes the high-quality utilization of waste acrylic fiber very feasible. Electrospinning technology is popular because of its fast production speed and simple and easy operation, which makes it have potential application prospects in the preparation of high performance (mechanical properties, ionic conductivity, etc.). Therefore, we tried to combine waste acrylic fiber with energy storage devices through electrospinning technology.
[0020] The invention firstly washes and dries the pre-recovered nylon; then, uniformly disperses the nylon, LLZTO and LiTFSI in an N,N-dimethylformamide solvent; obtains an organic-inorganic composite nanofiber membrane (nylon-LLZTO NFS) by an electrostatic spinning technology; finally, casts an organic-inorganic system (PEO / SN) mixed solution on the nylon-LLZTO NFS by a solution casting method to obtain a nylon-LLZTO composite solid electrolyte membrane, and the material can be applied to the energy storage field of flexible lithium-ion batteries.
[0021] The present invention recycles waste nylon in high quality, prepares nylon-LLZTO NFS by electrospinning with simple and low-cost process-controllable equipment, provides a 3D nanofiber framework, and improves the mechanical properties and flexibility of the electrolyte. The porous structure of NFS can be filled with a PEO-based electrolyte solution with high ionic conductivity, and the prepared composite solid electrolyte has multiple ion channels and excellent electrochemical properties.
[0022] The nitrile chloride, LiTFSI and LiDFOB used in the present invention participate in the formation of a solid electrolyte interface (SEI), forming a multi-component SEI to improve the cycle stability and inhibit the growth of lithium dendrites.
[0023] Preferably, the nylon in S1 needs to be washed and dried at a drying temperature of 60-80° C. When preparing the spinning solution, all raw materials must be dried. If the raw materials absorb water, the spinning solution cannot be prepared, spinning cannot be performed, or the electrochemical properties of the finished product may be affected.
[0024] Preferably, the stirring temperature of the electrospinning precursor solution is 35-80° C. This temperature range allows the chloronitrile to be completely dissolved to obtain a uniform solution.
[0025] Preferably, the weight ratio of nylon to LLZTO is 1:0.05-0.2, and the amount of LiTFSI added is 0.5-1.5% of the weight of nylon. The optimal weight ratio of nylon to LLZTO is 1:0.15.
[0026] Preferably, the electrospinning parameters are: an electrostatic voltage of 11-15 kV, a spinning distance of 9-12 cm, a flow rate of the electrospinning precursor solution of 0.4-0.7 mL / h, and a spinning drum speed of 170-250 rpm.
[0027] Preferably, in S3, all the solutes are polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB) and succinonitrile (SN); based on 100% by mass of PEO, the amount of SN is 20-60%. More preferably, based on 100% by mass of PEO, the amount of SN is 40-60%.
[0028] Preferably, the amount of LiTFSI is 25%-40%, and the optimal amount is 33%; the molar ratio of LiDFOB to LiTFSI is 1:19. Due to the high dissociation ability of LiTFSI and the excellent film-forming performance of LiDFOB, it is better to select these two lithium salts with PEO and SN to form a casting solution.
[0029] Preferably, the solvent in S3 is a PEO-soluble solvent such as acetonitrile or N,N-dimethylformamide, and the stirring time when PEO and the conductive lithium salt are mixed is 12-18 hours; the drying time of the composite solid electrolyte membrane in S4 is 7-12 hours.
[0030] Preferably, the total thickness of the composite solid electrolyte membrane is 90 μm-110 μm.
[0031] A chloronitrile-LLZTO composite solid electrolyte membrane prepared by the preparation method of the present invention.
[0032] An application of the chloronitrile fiber-LLZTO composite solid electrolyte membrane of the present invention in preparing a solid electrolyte or a solid lithium ion battery with flame retardant function.
[0033] The method of the present invention is easy to implement and can be mass-produced. The obtained organic-inorganic composite nanofiber membrane can form a three-dimensional ion-conducting path. The finally obtained nitrile-LLZTO composite solid electrolyte membrane with a dual lithium salt system has good tensile flexibility and can be bent and folded. When used as a solid electrolyte material for an all-solid-state lithium metal battery, it has good ion transmission capacity and can meet the needs of a long-life lithium metal battery.
[0034] In order to achieve high ionic conductivity and excellent mechanical flexibility of the composite solid electrolyte, an organic-inorganic composite nanofiber membrane (LLZTO NFS) can be prepared by electrospinning technology, and then compounded with a high ionic conductivity PEO / SN electrolyte solution to obtain a nylon-LLZTO composite solid electrolyte membrane. The continuous 3D ion-conducting path of the organic-inorganic composite nanofiber membrane is used to improve the overall ion-conducting effect of the solid electrolyte, and the PEO polymer matrix gives the overall mechanical flexibility; the selection of appropriate additives is conducive to destroying the order of PEO, reducing the crystallinity, enhancing the dynamics of the polymer chain segment, improving the ionic conductivity, and improving the electrode-electrolyte interface compatibility; in addition, during the charge and discharge process of the lithium metal battery, uniform lithium deposition is achieved to achieve stable ion transport. This composite solid electrolyte with both electrochemical performance and mechanical flexibility has broad application prospects in solid-state batteries.
[0035] Recycled nylon is usually blended with other fiber materials (such as cotton, wool, PET fiber) and contains dye materials, which may hinder their recycling. During the dissolution process, the blended fibers can be removed by filtration. The dyes do not need to be further processed, which greatly reduces the difficulty of recycling. First of all, the dyes used in these fabrics only account for 3% of the fabric mass at most, and most of the dyes used are azo dyes, which contain high nitrogen and can be used as a source of N in the electrolyte. In addition, the crystallinity of nylon after high-temperature dyeing is reduced, which is conducive to the improvement of electrochemical performance.
[0036] In summary, the method of the present invention has the following characteristics:
[0037] 1. Acrylic chlorofiber can be recycled for high quality, whether dyed or not, including acrylic chlorofiber fibers, yarns and fabrics;
[0038] 2. The present invention adopts an electrospinning method, which is simple to operate, and the reaction conditions are easy to control and implement, and is suitable for large-scale production;
[0039] 3. The nylon-LLZTO nanofiber membrane prepared by electrospinning has a continuous 3D ion-conducting path and ion channel, which significantly improves the mechanical properties and thermal stability of the nylon-LLZTO solid electrolyte;
[0040] 4. LLZTO organic filler improves the ionic conductivity of the electrolyte and promotes the uniform deposition of lithium ions. The dual lithium salt system forms a stable SEI layer at the interface between the electrolyte and the electrode, effectively inhibiting the side reaction between SN and the lithium negative electrode, which is beneficial to improving the ion transmission efficiency;
[0041] 5. The prepared nylon-LLZTO composite solid electrolyte membrane can be used in lithium metal batteries, wherein the LiCl generated by the nylon PVC segment in the SEI layer is more stable and efficient than LiF, which significantly improves the stability of the battery interface and prolongs the cycle life of the battery; the flame retardant property of nylon makes the nanofiber membrane and electrolyte prepared by the process of the present invention using it as a polymer raw material have heat resistance;
[0042] 6. The prepared nylon-LLZTO composite solid electrolyte membrane has practical application value in flexible soft-pack batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is a scanning electron microscope (SEM) photograph of the surface of the nylon-LLZTO nanofiber membrane prepared in Example 1;
[0044] Figure 2 is a scanning electron microscope (SEM) photograph of the nylon-LLZTO composite solid electrolyte membrane prepared in Example 1;
[0045] Figure 3 The polarization curve diagram (left) and the interface resistance diagram before and after polarization (right) of the Li / solid electrolyte / Li symmetric battery of the nylon-LLZTO composite solid electrolyte membrane prepared in Example 1 are shown;
[0046] Figure 4 This is a test diagram of the Li / solid electrolyte / Li symmetric battery cycle stability of the nylon-LLZTO composite solid electrolyte membrane prepared in Example 1;
[0047] Figure 5 The electrochemical impedance spectroscopy (EIS) graph (left) and the enlarged graph (right) of the impedance graph of the stainless steel / solid electrolyte / stainless steel symmetric battery of the nylon-LLZTO composite solid electrolyte membrane prepared in Example 1 at different temperatures;
[0048] Figure 6 This is the XPS test spectrum of the surface of the nylon-LLZTO composite solid electrolyte membrane before and after the cycle;
[0049] Figure 7 The polarization curve diagram (a) and the interface resistance diagram before and after polarization (b) of the Li / solid electrolyte / Li symmetric cell of the nylon-LLZTO composite solid electrolyte membrane prepared in Comparative Example 1;
[0050] Figure 8 This is a test diagram of the Li / solid electrolyte / Li symmetric battery cycle stability of the nylon-LLZTO composite solid electrolyte membrane prepared in Comparative Example 1;
[0051] Fig. 9The polarization curve diagram (left) and the interface resistance diagram before and after polarization (right) of the Li / solid electrolyte / Li symmetric battery of the nylon-LLZTO composite solid electrolyte membrane prepared in Comparative Example 2 are shown;
[0052] Fig.10 This is a test diagram of the Li / solid electrolyte / Li symmetric battery cycle stability of the nylon-LLZTO composite solid electrolyte membrane prepared in Comparative Example 2;
[0053] Fig.11 This is the Arrhenius plot measured after adding different LLZTO contents to the nylon-LLZTO composite solid electrolyte membrane prepared in Example 3;
[0054] Fig.12 This is the Arrhenius plot measured for the chloronitrile-LLZTO composite solid electrolyte membrane prepared by adding different mass fractions of SN to the PEO-SN casting solution of Comparative Example 4;
[0055] Fig.13 These are the combustion test diagrams of nanofiber membranes made of PAN powder and nylon respectively;
[0056] Fig.14 It is a microcalorimeter test of the composite solid electrolyte made of PAN powder and nylon and the solid electrolyte of Comparative Example 1;
[0057] Fig.15 This is a diagram of the preparation process of the colored nylon-LLZTO composite solid electrolyte membrane prepared in the application example;
[0058] Fig.16 This is an application diagram of the colored nitrile-LLZTO composite solid electrolyte membrane prepared in the application example for preparing soft-pack batteries;
[0059] Fig.17 This is a diagram of the application of the colored nitrile-LLZTO composite solid electrolyte membrane prepared in the application example to prepare soft-pack batteries at low temperatures. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0061] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0062] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.
[0063] Example 1 (Best Case)
[0064] A method for preparing a nylon-LLZTO composite solid electrolyte membrane using waste nylon material, the specific steps of the method are as follows:
[0065] (1) Cleaning of waste nylon: Wash the pre-recovered waste nylon under running water for 10 minutes, then add an appropriate amount of ethanol (to submerge the nylon) and soak for 10 hours. Take it out and place it in a vacuum oven for drying.
[0066] (2) Preparation of organic-inorganic composite nanofiber membrane: Weigh 1 g of cleaned nitrile, 0.15 g of LLZTO, and 0.1 g of LiTFSI and dissolve them in 5 g of N,N-dimethylformamide solvent and stir them evenly at 50°C to obtain an electrospinning precursor solution; under the spinning conditions of an electrostatic voltage of 13 kV, a spinning distance of 9 cm, a spinning solution flow rate of 0.6 mL / h, and a drum speed of 200 rpm, the precursor solution is spun into a nanofiber membrane, and then vacuum dried at 50°C to evaporate the residual liquid, taken out and placed in a glove box filled with argon for standby use, to obtain an organic-inorganic composite nanofiber membrane (nitrile-LLZTO NFS);
[0067] (3) Preparation of electrolyte solution: First, polyethylene oxide (PEO), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB) and SN were vacuum dried at 40°C for later use; then, PEO and LiTFSI were dissolved in acetonitrile at a molar ratio of EO:Li=20:1, the molar ratio of LiDFOB to LiTFSI was 1:19, and SN accounted for 40% of the mass of PEO; finally, the mixture was stirred at room temperature for 15 h to form a uniform mixed solution, thereby obtaining an electrolyte solution of the PEO / SN system.
[0068] (4) Preparation of composite solid electrolyte membrane: First, the electrolyte solution of the PEO / SN system in step (3) is sucked with a syringe; then, the organic-inorganic composite nanofiber membrane (nitrile-LLZTO NFS) obtained in step (2) is placed on a polytetrafluoroethylene mold, and then a layer of the electrolyte solution of the PEO / SN system is poured until it is completely permeated; finally, after the acetonitrile in the electrolyte solution of the PEO / SN system is completely volatilized, the nitrile-LLZTO composite solid electrolyte membrane is removed and vacuum dried at 50° C. for 10 hours to obtain the final composite solid electrolyte. The total thickness of the composite solid electrolyte membrane is controlled to be 90-110 μm.
[0069] The prepared nylon-LLZTO NFS has a three-dimensional multi-porous structure ( Figure 1) can be filled with PEO / SN electrolyte solution with good fluidity. After casting, the acrylic chlorofiber-LLZTO SPE has a flat surface without protrusions ( Figure 2 ), achieving good contact between the electrolyte and the Li metal, and promoting the transport of lithium ions at the interface; the polarization test curve of the prepared nitrile chlorinated fiber-LLZTO SPE Li / solid electrolyte / Li symmetric battery is shown in Figure 3 , the ion mobility reaches 0.84 at 50°C; and during the charge and discharge process, after >2500h, 100μAcm -2 The Li / solid electrolyte / Li symmetric cell can still operate stably under the current density of electroplating / stripping cycles, and the polarization voltage does not increase significantly ( Figure 4 The electrochemical impedance spectroscopy (EIS) of the stainless steel / solid electrolyte / stainless steel battery of the prepared nylon-LLZTO SPE is shown in Figure 5 The calculated ionic conductivity at 30°C is 1.7x10 -3 S cm -1 , improving the electrochemical performance of solid-state lithium metal batteries.
[0070] X-ray photoelectron spectroscopy (XPS) was further used to characterize the composition of SEI. Figure 6 The XPS spectra of the initial electrolyte and the electrolyte surface after cycling in a lithium symmetric battery were compared. The new peaks at 684 eV of F1s and 530 eV of O1s after cycling belong to the formed LiF and LiOH, respectively. This means that both LiTFSI and LiDFOB decomposed on the lithium surface during the cycling process to form a SEI layer. There were four obvious C1 2p peaks in the electrolyte before cycling, indicating that Cl existed in two forms, LiCl and C-Cl bonds. After cycling, the main form of Cl on the electrolyte surface was LiCl, proving that the organic chlorine of nitrile during the cycling process participated in the construction of SEI to form metal chloride compounds (LiCl). The SEI layer formed in situ between the electrolyte and lithium metal is stable enough to inhibit the growth of lithium dendrites and prevent adverse reactions between SN and lithium metal.
[0071] Comparative Example 1
[0072] The difference from Example 1 is:
[0073] In step (2), LLZTO is not added when preparing the spinning solution to prepare chloronitrile fiber NFS.
[0074] The polarization test curve of the prepared LLZTO-free nylon SPE Li / solid electrolyte / Li symmetric battery is shown in Figure 7 , the ion mobility at 50°C is only 0.63, and the ion transmission capacity is worse than that of Example 1 ( Figure 8 ).
[0075] Comparative Example 2
[0076] The difference from Example 1 is:
[0077] Steps (1) and (2) were eliminated, and the PEO / SN electrolyte solution prepared in step (3) was cast on a polytetrafluoroethylene mold. After the acetonitrile in the PEO / SN electrolyte solution was completely volatilized, the PEO / SN SPE was removed and vacuum dried at 50° C. for 24 h to obtain the solid electrolyte of Comparative Example 2. The total thickness of the solid electrolyte membrane was controlled to be 90-110 μm.
[0078] The prepared PEO / SN Li / solid electrolyte / Li symmetric battery has an ion mobility of only 0.43 ( Fig. 9 ), the ion transmission capacity is poor. After about 150h, a short circuit occurs ( Fig.10 ).
[0079] Comparative Example 3
[0080] The difference from Example 1 is:
[0081] In step (2), the content of LLZTO was changed to 0, 0.05, 0.10, 0.15 and 0.20 g respectively (the figure numbers in the figure are distinguished by abbreviations, such as 0.05 is abbreviated as 5, and 0.10 is abbreviated as 10) to prepare different chloronitrile-LLZTO NFS.
[0082] The ionic conductivity of nylon-LLZTO SPE with different LLZTO contents was compared ( Fig.11 ). As the LLZTO content increases, the ionic conductivity of the stainless steel / solid electrolyte / stainless steel symmetric battery also increases. However, when the LLZTO content is 0.2g, the ionic conductivity of the stainless steel / solid electrolyte / stainless steel symmetric battery decreases. This may be because excessive ceramic fillers will cause agglomeration and hinder ion transport. Therefore, the optimal weight ratio of nitrile chlorinated fiber to LLZTO is 1:0.15.
[0083] Comparative Example 4
[0084] The difference from Example 1 is:
[0085] Taking the mass of PEO as 100%, the content of SN in step (3) was changed to 0, 20, 40, 60 and 80% to prepare different PEO / SN casting solutions.
[0086] The ionic conductivity of chloronitrile-LLZTO CSE with different SN contents was compared ( Fig.12). As the SN content increases, the ionic conductivity increases significantly. However, when the SN addition increases from 40wt% to 60wt% of PEO, the ionic conductivity does not increase significantly. When the SN addition continues to increase to 80wt%, the ionic conductivity decreases instead, because the excessive SN filler causes the PEO amorphous phase to decrease, forming a discontinuous Li + Therefore, it is considered that the optimal amount of SN added is 40-60wt% of PEO.
[0087] Comparative Example 5
[0088] The difference from Example 1 is:
[0089] The PAN-LLZTO NFs were prepared by replacing the nylon with PAN powder in the same process, and the PLCSE was obtained by pouring the PN casting solution.
[0090] The flame retardant properties of different fiber membrane materials were tested. The results showed that ( Fig.13 ) WML NFs shrink rapidly under the action of flames and automatically extinguish without continuing to burn or smolder. This is because the HCl released by the chlorine element in WML NFs during combustion can effectively inhibit further combustion. Microcalorimeter (MCC) was further used to test the safety performance of the electrolyte. Fig.14 The peak heat release rate (PHRR) and heat release amount (THR) of different electrolytes are shown. PAN is a flammable polymer with low thermal stability. Even Example 5: PAN-LLZTO CSE (PLCSE) prepared by the process of the present invention still has a high PHRR (241.531 W / g), but the PHRR (119.816 W / g) of the WML CSE prepared in Example 1 is only half of that of the PL CSE. It is worth noting that even Comparative Example 1 (WM SPE) without the addition of LLZTO has a lower PHRR (201.144 W / g). Similarly, the THR of WML CSE and WM SPE is reduced from 14 of PLCSE to 10.7 KJ / g and 13.5 KJ / g. The above results show that the electrolyte prepared using waste nylon copolymerized with PAN and PVC has better heat resistance than PAN, and the successful addition of LLZTO further improves the thermal stability of the composite solid electrolyte. These results demonstrate that the use of acrylic fibers provides a safer working environment for lithium-ion batteries than PAN (or acrylic fibers prepared from PAN).
[0091] Application example: Packaging of soft pack batteries
[0092] The difference from Example 1 is:
[0093] In step (1), colorless, red, yellow and blue nylon are washed and dried respectively for later use.
[0094] In step (2), 1 g of nylon was weighed, wherein the weight ratio of colorless nylon, red nylon, yellow nylon and blue nylon was 1:3:3:3. Dyed nylon-LLZTO NFS was prepared for the subsequent step of preparing dyed nylon-LLZTO SPE.
[0095] Prepare a LiFePO4 coated positive electrode (larger than the lithium sheet), cut a 3×3 cm lithium sheet in a glove box, and prepare two electrodes. Heat the two pole ears in the electrode to make the electrode and dyed nitrile-LLZTO SPE (preparation diagram as shown in the figure) Fig.15 ) are bonded and packaged together in aluminum foil (heating times: 3-5 times). It is particularly important to ensure that the vacuum in the aluminum foil is completely evacuated during the packaging process (vacuuming times: 5-7 times) to prevent the lithium sheet from oxidizing. In order to reflect the cycle stability of the dyed nitrile chlorinated fiber-LLZTO composite solid electrolyte membrane provided by the present invention in the soft-pack battery, the two poles are first connected to the positive and negative electrodes of the LED lamp respectively, thereby lighting it up, and its safety performance is tested in the soft pack. The on-site photos are shown in FIG. Fig.16 As shown, the brightness of the LED lamp is not affected, proving that the composite solid electrolyte has good cycle stability. The soft pack battery is placed in an ice bag environment and can still power the LED lamp after being left still. ( Fig.17 )
[0096] The above experiments fully prove that the prepared nitrile chloride-LLZTO composite solid electrolyte membrane can greatly improve the electrochemical performance of solid-state lithium metal batteries, and can be actually used in the preparation of flexible solid-state lithium batteries.
[0097] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0098] The above is a detailed introduction to the method for preparing a nylon-LLZTO composite solid electrolyte membrane using waste nylon materials provided by the present invention and its application. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a nylon-LLZTO composite solid electrolyte membrane using waste nylon materials, characterized in that The method comprises the following steps: S1. Cleaning of waste acrylic fiber The dyed or colorless acrylic fiber, yarn or fabric (collectively referred to as acrylic fiber) to be recycled is washed with running water to remove impurities, then immersed in anhydrous ethanol for 12 h-15 h, and vacuum dried to obtain clean acrylic fiber; S2. Preparation of organic-inorganic composite nanofiber membrane Adding S1 treated nylon, inorganic ceramic filler LLZTO and lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) into solvent N,N-dimethylformamide (DMF), and stirring them fully at a temperature of 35-80 °C to obtain a uniformly mixed spinning precursor solution; wherein the weight ratio of nylon to LLZTO is 1:0.02-0.3, and the addition amount of LiTFSI accounts for 0.2-3% of the mass of nylon; The spinning precursor solution is electrospun to prepare a nylon / LLZTO nanofiber membrane, and then dried in vacuum at 45±5° C. to obtain an organic-inorganic composite nanofiber membrane; S3. Preparation of electrolyte solution Polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB) and succinonitrile (SN) are dried in vacuum within a suitable temperature range and then used. PEO, LiTFSI and LiDFOB are uniformly stirred in an appropriate amount of solvent until they are completely dissolved, and then SN is added and stirred until uniformly dispersed to obtain a dual lithium salt PEO-based electrolyte solution; Based on the mass of PEO as 100%, the amount of SN is 10-80%, the amount of LiTFSI is 10%-50%, and the molar ratio of LiDFOB to LiTFSI is 1:18-20. S4. Preparation of composite solid electrolyte membrane The organic-inorganic composite nanofiber membrane prepared in S2 is placed on a polytetrafluoroethylene mold, and a layer of electrolyte solution prepared in S3 is cast on the surface; after the solvent is completely evaporated, vacuum drying is performed at a temperature of 40-50°C to obtain a nitrile-LLZTO composite solid electrolyte membrane of a dual lithium salt system.
2. The method according to claim 1, characterized in that: The nylon in S1 needs to be washed and dried at a temperature of 60-80 °C.
3. The method according to claim 1, characterized in that: The weight ratio of nylon to LLZTO is 1:0.05-0.2, and the added amount of LiTFSI is 0.5-1.5% of the mass of nylon.
4. The method according to claim 1, characterized in that: The parameters of electrospinning are electrostatic voltage 9-16 kV, spinning distance 8-13 cm, flow rate of electrospinning precursor solution 0.2-0.9 mL / h, and spinning drum speed 150-280 rpm.
5. The method according to claim 1, characterized in that: The total thickness of the composite solid electrolyte membrane is 90 μm-110 μm.
6. The method according to claim 1, characterized in that: In S3, all solutes are polyethylene oxide (PEO), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB) and succinonitrile; based on the mass of PEO being 100%, the amount of SN is 20-60%.
7. The method according to claim 1, characterized in that: The dosage of LiTFSI is 25%-40%; the molar ratio of LiDFOB to LiTFSI is 1:
19.
8. The method according to claim 1, characterized in that: The solvent in S3 is acetonitrile or N,N-dimethylformamide, and the stirring time when PEO and the conductive lithium salt are mixed is 12-18 hours; the drying time of the composite solid electrolyte membrane in S4 is 7-12 hours.
9. A chloronitrile-LLZTO composite solid electrolyte membrane prepared by the method according to claim 1.
10. Use of the nylon-LLZTO composite solid electrolyte membrane according to claim 1 in preparing a solid electrolyte or a solid lithium ion battery with flame retardant function.
Citation Information
Patent Citations
Nanofiber polyvinylidene fluoride-based composite solid electrolyte and preparation method and application thereof
CN114094179A
Lighting equipment inspection system
KR102117707B1
Cited By
Preparation method of negative-electrode-free PEO-based solid-state lithium-sulfur battery
CN120089809A
